Bangladesh : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper reviews Bangladesh's recent growth experience and per capita income. The paper identifies several key impediments to growth, namely: poor governance; restrictive trade and regulatory regimes; and inadequate investment in human capital and physical infrastructure. The paper makes the case that the medium-term fiscal strategy should be centered on boosting the revenue performance of the National Board of Revenue (NBR) by reorganizing it along functional lines, adopting a system of self-assessment, establishing a risk-based auditing system, and introducing a unique taxpayer identification number.